Characterization of geopolymer composites for 3D printing: a microstructure approach - Youssef, Passant; El-Feky, Muhammad S.; Ragab, Ahmed M.; Serag, Mohamed I. (Innovative infrastructure solutions : the official journal of the Soil-Structure Interaction Group in Egypt (SSIGE), 2024)
Given the importance of geopolymer in terms of 3D printing performance and the scarcity of information on the subject, as well as previous research findings, the purpose of this study is to propose a design methodology for geopolymer concrete mix that can be used in the 3D printing process by studying the effect of fine aggregate size and type, binder type (either slag or metakaolin) and ratio (slag/metakaolin), and alkaline solution amount and ratio (NaOH/Na2SiO3). The study concluded that MK has lower fluidity than BFS under the same conditions that used the same amount of SP. However, it can be improved by adding slag. The best dosage was chosen, which is 50% MK and 50% BFS. Because of these proportions, the mixture is very dense, homogeneous and compact, which increases its microstructure analysis behavior.